Improving Safety Risk Analysis Through The Application Of Case Based Reasoning Concepts - Goh Y.M. (2018)
Innovative developments in architecture, engineering and construction : proceedings of the 2nd International Conference on Innovation in Architecture, Engineering and Construction, Loughborough, United Kingdom, 25-27th June, 2003